Dr Locus of Control: An Appraisal of Employees’ Job Satisfaction in the Nigerian Service Industry: Locus of Control: An Appraisal of Employees’ Job Satisfaction in the Nigerian Service Industry (Journal of Economic Research & Business Administration, 2021)
Understanding what controls an individual’s outcome and balancing an individual’s perception oflocus of control with work-life has been the major concern over the years. Hence, this study examinedthe influence of locus of control on the job satisfaction of employees. A survey research design was adoptedfor this study. A structured questionnaire was administered to collect data from 309 employees ofthe selected organization. Inferential statistics was used to analyze the data, while the hypotheses weretested by correlation and regression. The result revealed a positive significant effect of work enthusiasm(R2 = 0,576; P = 0,000), psychological states (r = 0,805; P < 0,05), personality traits (R2 = 0,438; P =0,000) on job satisfaction. The study concludes that locus of control variables are the major determinantof employees’ job satisfaction, and if not properly managed and controlled, it could affect the overallorganizational performance. Therefore, managers should ensure the right person with the right emotionaland intellectual capabilities are appointed to various positions to forestall employees’ low morale andineffectiveness.Key words: locus of control, job satisfaction, personality traits, work enthusiasm, reinforcement.